Analisis Manajemen Risiko Pada UMKM “Angkringan Pandewa” Jl. Sindanglaya Bandung - Yunawwirudin Haq, Fajar; Dimas, Muhammad Satria; Mustofa, Rizal (Universitas Serambi Mekkah, 2024)
Micro, Small and Medium Enterprises (MSMEs) are the main pillars of the economy in Indonesia, making a significant contribution to labor absorption and local economic development. This research aims to examine the role, challenges and development strategies of MSMEs in facing market dynamics. Using a qualitative approach through literature studies and observations, this research found that MSMEs face challenges such as limited capital, access to technology and market competitiveness. Strategic solutions such as digitalization, increased management skills, and collaboration with the government or related institutions can be the key to the desires and growth of MSMEs